2000
DOI: 10.1097/00006231-200008000-00002
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET in the evaluation of the aggressiveness of pulmonary adenocarcinoma: correlation with histopathological features

Abstract: 2-[Fluorine-18]fluoro-2-deoxy-d-glucose (FDG) uptake within the primary lesion correlates with survival on positron emission tomography (PET) studies of patients with non-small cell lung cancer. The more metabolically active the tumour, the worse the outcome. The aim of this study was to determine whether a correlation exists between aggressiveness as determined by pathology and the findings of FDG PET in pulmonary adenocarcinoma. Thirty-five patients with 38 adenocarcinomas of the lung were studied. All patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 14 publications
3
51
0
4
Order By: Relevance
“…In pulmonary adenocarcinoma, it has been reported that cases with high FDG uptake have a lower 5-year survival rate than those with a low FDG uptake, and also show poorer prognosis. 11 In addition, in nonsmall cell lung carcinoma, it has been reported that FDG uptake is an independent prognostic factor, giving values similar to those obtained from pathologic staging. 9 Uptake of FDG has been shown to correlate with the proliferative rate in lung carcinoma.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In pulmonary adenocarcinoma, it has been reported that cases with high FDG uptake have a lower 5-year survival rate than those with a low FDG uptake, and also show poorer prognosis. 11 In addition, in nonsmall cell lung carcinoma, it has been reported that FDG uptake is an independent prognostic factor, giving values similar to those obtained from pathologic staging. 9 Uptake of FDG has been shown to correlate with the proliferative rate in lung carcinoma.…”
Section: Discussionmentioning
confidence: 61%
“…[7][8][9][10][11] Markedly increased FDG uptake in esophageal squamous cell carcinoma (SCC) has been documented in several studies, [12][13][14][15] and they have reported that PET using FDG shows greater sensitivity in the diagnosis of involved regional lymph nodes than computed tomography (CT). This suggests that PET may have a role in evaluating the stage of esophageal carcinoma.…”
mentioning
confidence: 99%
“…In addition, the uptake of FDG in the primary tumor reflects some biological information, including proliferative activity (20), tumor doubling time (21), microvessel density (22), histological subtype (17,18) and tumor grading (17). In the present study, the FDG uptake and MTV of the primary tumor were significantly different among subgroups by differentiation in both AC and SCC.…”
Section: No Of Lymph Nodes (N=812)mentioning
confidence: 52%
“…In another study this group found that those adenocarcinomas with more invasive features (i.e. poorly differentiated tumors) had greater FDG uptake (SUV 4.36±1.94) compared to non-invasive tumors (SUV 1.53±0.88) (22). Additionally, they found that patients with tumors with greater FDG uptake had a poorer prognosis.…”
Section: Discussionmentioning
confidence: 95%